2006
DOI: 10.1007/s10689-005-2832-5
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2: Chemosensitivity, Treatment Outcomes and Prognosis

Abstract: BRCA1 and BRCA2 are important breast and ovarian cancer susceptibility genes, and mutations in these two genes confer lifetime risks of breast cancer of up to 80% and ovarian cancer risks of up to 40%. Clinico-pathological studies have identified features that are specific to BRCA1-related breast cancer, but this has been more difficult for BRCA2-related breast cancer. Ovarian cancers due to BRCA1 or BRCA2 mutations cannot usually be distinguished from their non-hereditary counterparts on morphological grounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 79 publications
5
84
0
3
Order By: Relevance
“…The hypersensitivity to ICL inducers observed in our cell models is consistent to what previously reported for the HCC1937 cell line (in which this phenotype was reversed by ectopic restoration of BRCA1 expression) and is in line with the observation that BRCA1 defects represent favorable prognostic factors for ovarian cancer patients treated with platinum compounds (34)(35)(36).…”
Section: Discussionsupporting
confidence: 92%
“…The hypersensitivity to ICL inducers observed in our cell models is consistent to what previously reported for the HCC1937 cell line (in which this phenotype was reversed by ectopic restoration of BRCA1 expression) and is in line with the observation that BRCA1 defects represent favorable prognostic factors for ovarian cancer patients treated with platinum compounds (34)(35)(36).…”
Section: Discussionsupporting
confidence: 92%
“…36 In contrast, cancer cells deficient in HR (e.g., breast tumors with BRCA2 mutations 37,38 ) are rendered sensitive to chemotherapeutic agents that induce replication fork breakdown. [39][40][41][42] Therefore, knowledge about HR capacity is relevant both to one's risk of developing cancer 13,14,19 and to the response of a tumor to chemotherapy. [39][40][41][42][43] Although HR is an important pathway for overcoming the potential lethality and mutagenicity of replicative stress, studying HR has been difficult since many key HR proteins are either essential for viability [44][45][46][47][48][49] or possibly sufficiently redundant that their absence does not fully reveal the role of this pathway in vivo.…”
Section: Homologous Recombination Modulates Cytotoxicity and Genomic mentioning
confidence: 99%
“…A subsequent systematic review by (Stordal et al 2009), revealed that BRCA1 was the mostly likely genetic player in this relationship. Cells with BRCA1 defects have reduced efficiency in repairing DNA adducts and show increased apoptosis in response to platinums conferring sensitivity (Foulkes 2006;Xing et al 2006). The response to taxanes, in BRCA1 deficient cells is reduced apoptosis conferring resistance (Lafarge et al 2001).…”
Section: Introductionmentioning
confidence: 99%